Pola Integrasi Sains dan Islam dalam Pembelajaran Biologi ; Kajian Kompetisi Sains Madrasah (KSM) Mata Pelajaran Biologi Terintegrasi di MAN 1 Wonosobo - Syarif Hidayat; Nurul Mubin; Faisal Kamal (CV. Aksara Global Akademia, 2025)
This study aims to explore the integration pattern between Science and Islam in the context of the Integrated Madrasah Science Competition (KSM) for Biology at MAN 1 Wonosobo. The research specifically seeks to: (1) identify the conceptual pattern of Science–Islam integration in Biology learning, (2) examine the implementation of this integration in the KSM preparation process, and (3) analyze the factors influencing its effectiveness. This research adopts a qualitative approach, employing field research and descriptive analysis to capture a comprehensive understanding of the phenomenon. The findings reveal that the integration pattern in Biology learning within the KSM context is characterized as integrative–interconnective, where scientific concepts are interconnected with Islamic values and perspectives. Supervisory teachers with a strong background in pure Biology tend to be more active in developing discussion themes, conducting in-depth dialogues, and organizing studies that merge scientific and religious viewpoints. The effective implementation of this integration is supported by optimal utilization of learning resources, particularly Biology textbooks, as a source of pure scientific material enriched with Islamic insights. Such integration is further strengthened by collaborative discussions between teachers and students, fostering deeper understanding and critical thinking. Several factors contribute to the effectiveness of Biology KSM learning. These include the existence of a curriculum and learning materials that intentionally integrate Science and Islam, as well as the interdisciplinary competencies of teachers who not only master Biology content but also possess the ability to connect it with Islamic principles. Additionally, institutional support from all components of the madrasah—administrators, fellow teachers, and students—plays a crucial role in creating a structured, motivating, and inspiring guidance environment. In conclusion, the integration of Science and Islam in the Biology KSM at MAN 1 Wonosobo represents an effective educational model that promotes both scientific literacy and religious understanding, contributing to holistic student development in madrasah education.